Pengembangan Asesmen Formatif Berbasis Wordwall Materi Kalimat Majemuk Setara di Kelas 4 SDN 03 Pontianak Selatan - Akbar, Anugrah; Hairida, Hairida; Priyadi, Antonius Totok; Halidjah, Siti; Safrianty, Nany (Jurnal PGSD, 2025)
This study aims to develop a Wordwall-based formative assessment for compound-equivalent sentences, by testing the feasibility of the product based on validity and feedback from teachers and students. Using a developmental research approach with the ADDIE model, this study was limited to the development stage. Quantitative data were obtained from expert validation results and questionnaire responses from teachers and students, supplemented by qualitative insights from the validator. Data collection involved interviews and questionnaires, using tools such as interviews, validation sheets, and questionnaire responses. Participants consisted of three teachers and 25 fourth-grade D students at SDN 03 South Pontianak. Validation by material experts, linguists, and media experts each resulted in a score of 1.0, indicating "very high validity" according to Gregory's formula. Questionnaire responses showed a teacher rating of 91% and a student rating of 88%, both of which fall into the "very good" category. The development of a Wordwall-based formative assessment for compound-equivalent sentences demonstrated very high validity and received very positive feedback from both teachers and students.